Does Hotter Temperature Increase Poverty? Global Evidence from Subnational Data Analysis - Hai-Anh H. Dang; Trong-Anh Trinh (Global Labor Organization (GLO), 2022)
Despite a vast literature documenting the negative effects of climate change on various socio-economic outcomes, surprisingly hardly any evidence exists on the global impacts of hotter temperature on poverty. Analyzing a new global dataset of subnational poverty in 166 countries, we find higher temperature to increase poverty. This finding is robust to various model specifications, data samples, and measures of temperature. Our preferred specification shows that a 1°C increase leads to a 2.1 percent increase in the headcount poverty rate, using the US 1.90 daily poverty threshold. Regional heterogeneity exists, with Sub-Saharan African countries being most vulnerable to higher temperature. We find suggestive evidence that reduction in crop yields could be a key channel that explains the effects of rising temperature. Further simulation indicates that global warming can significantly increase poverty, with more pronounced effects occurring in poorer regions and under scenarios of higher greenhouse gas emissions without mitigation policies.
Keywords: Q54; I32; O1; 330; climate change; global warming; poverty; agriculture; subnational data